Alkaloids and inhibitory effects against enzymes linked to neurodegenerative diseases (physostigmine, galanthamine, huperzine, etc.) - Orhan, I. E.; Deniz, F. Sezer Senol (Springer Berlin Heidelberg, 2013)
Alkaloids are one of the largest natural products with low molecular weight found in plants, fungus, animals, and microorganisms. Many reports have confirmed that alkaloids have a desired therapeutic potential against human diseases. Acetylcholinesterase (AChE, EC 3.1.1.7) is an enzyme that has ability to inhibit the hydrolysis of the neurotransmitter called acetylcholine and elevate its level in the synaptic cleft, associated with several neurological disorders such as mostly Alzheimer’s disease (AD) and myasthenia gravis. AChE inhibition in addition to butyrylcholinesterase (BChE) has been the most widely accepted treatment strategy against AD, which is characterized by shortage of acetylcholine in the brain. The current AChE inhibitors used in clinical application (rivastigmine, donepezil, and galanthamine) are classified under alkaloids, and consequently, alkaloids have become a popular target in discovery of novel cholinesterase inhibitors. In this chapter, current cholinesterase-inhibiting alkaloids of natural origin (physostigmine, galanthamine, and huperzine A) will be mentioned in addition to some promising ones with marked cholinesterase inhibition. © Springer-Verlag Berlin Heidelberg 2013.
Keywords: Acetylcholinesterase; Alkaloid; Alzheimer’s disease; Cholinesterase; Plant